MACRO-ECONOMIC IMPACT ON STOCK PRICES - Toufiq Agung Pratomo Sugito Putra; Sugiyanto Sugiyanto (JRAK, 2021)
Macroeconomics is an integral component of economic activity. The goal of this research is to demonstrate the effects of the macro-economic effect on stock returns with a more focused and tailored scope of the financial sector. This research uses a quantitative methodology with mathematical techniques, data used in the period 2001-2018, time series models with Vector Autoregressive (VAR) approaches where the data used are stationary and not co-integrated. The VAR model shows that if there is a parallel interaction between the measured variables, these variables can be considered similarly so that there are no more endogenous and exogenous variables. The findings showed that inflation, exchange rates and interest rates have no significant effect while economic growth had an impact on stock returns in the financial sector on the Indonesian stock exchange in 2001-2018.